UMP commitment to the Sustainable Development Goals SDGs Initiative - Muhammad Aizat, Azed (2021)
KUANTAN, 22 November 2021 – Lestari Unit, Universiti Malaysia Pahang (UMP) organised a webinar on UMP Commitment to the Sustainable Development Goals (SDGs) Initiative under Malaysian Sustainable University Campus Network Universiti Malaysia Pahang, (MYSUN-UMP) project co-funded by Erasmus+ programme of European Union.